Graduate employability, employment prospects and work-readiness in the changing field of professional work. Issue 2 (July 2020) - Herbert, Ian P.; Rothwell, Andrew T.; Glover, Jane L.; Lambert, Stephanie A.
Abstract: In the light of emerging challenges to traditional employment patterns, not least, global competition for 'location free' professional work, the Higher Education sector is facing increasing demands for graduates to transition more effectively from education to work. Accordingly, the paper draws on Bourdieu's account of practice and the process of 'culturing' to explore the application of those personal behaviours and dispositions that go beyond the observable knowledge and employability credentials that, typically, are conferred by a university degree. Of particular concern is the role of the shared service centre model in the elimination, automation and offshoring of those entry-level tasks that, traditionally, have provided routes into professional careers. Empirical findings suggest that the process of culturing could provide a game playing advantage in securing graduate employment through the projection of work-readiness. A call is made for management educators, employers, government and professional bodies to think more creatively in fostering student behaviours and dispositions in work-based learning alongside, rather than at the expense of, developing intellectual skills and subject knowledge. Highlights: Global competition for entry-level professional work is increasing. Graduates need to transition effectively and quickly into work. Personal behaviours and dispositions go beyond normal degree credentials. The process of culturing could provide a game playing advantage in work-readiness. Educators need to foster student behaviours and dispositions in work-based learning.